Understanding chemistry professors' use of educational technologies: An activity theoretical approach - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2008)
The aim of this study is to understand the influences on chemistry professors' use of educational technology. For this, we use activity theory to focus on two university chemistry professors and the broader activity system in which they work. We analyse their beliefs and past experiences related to teaching, learning, and technology as well as other components of the activity system of teaching chemistry with understanding. We employ a qualitative methodology with phenomenological and symbolic interactionist perspectives. Our findings illustrate various contradictions within and between the components of the activity system. Those include the insufficient level of collaboration, reflection, and communication among faculty members, constraints for reform-based chemistry teaching, limitations of large class sizes, and poor design of technology-enhanced classrooms. We propose several possible resolutions to transform undergraduate chemistry education, including the effective utilization of technology-enhanced teaching strategies and building a more uniform culture of teaching within science content departments.
Keywords: SCIENCE